Експериментальне дослідження компактної системи охолодження з тепловими трубами для потужної світлодіодної матриці - Pekur, Demyd; Sorokin, Viktor; Nikolaenko, Yurii (PE "Politekhperiodika", Book and Journal Publishers, 2020)
LED light sources, and powerful multichip light sources in particular, are currently widely used for lighting household and industrial premises. With an increase in power, the amount of heat increases as well, which leads to an increase in the temperature of semiconductor crystals and, accordingly, to a decrease in the reliability of LEDs and a change in their photometric characteristics. Therefore, when developing the design of LED lighting devices, special attention is paid to thermal management. Since the early 2000s, heat pipes have been widely used to efficiently remove heat from powerful electronic components. They do not require power for moving the working fluid and are most suitable for use in LED luminaires.In this study, the authors carry out a computer simulation of a cooling system based on heat pipes, which is then used to design and test a powerful compact LED lamp with a thermal load of up to 100 W.Heat pipes with a length of 150 mm are used to remove heat from the LED light source to the heat exchanger rings located concentrically around it. The heat exchanger rings are cooled by natural convection of the ambient air. The results of computer modeling of the temperature field of the developed cooling system show that at a power of the LED light source of 140.7 W, the temperature of the LED matrix case is 60.5В°C, and the experimentally measured temperature is 61.3В°C. The experimentally determined thermal power of the LED matrix is 91.5 W. The p-n junction temperature is 79.6В°C. The total thermal resistance of the cooling system is 0.453В°C/W. The obtained results indicate the effectiveness of the developed design.